Comparative analysis of regional unemployment and RGDP in Croatia and selected transition countries - Jelena Šišinaèki; Ivana Rasic; Valerija Botric (European Regional Science Association (ERSA), 2004)
Most transition economies have experienced a prolonged periods of high unemployment rates and decline of the growth rates at the beginning of transition process. However, after the initial decline in the economic activity, a period of stronger growth rates was recorded in most of the transition countries. Many analyses were done on this initial phase of transition process so we are concentrating on more successful period of transition process. Through the analysis of a regional gross domestic product dynamics in Croatian regions and several other European Union Candidate Countries we are identifying common development patterns in selected countries. Furthermore, since the unemployment is severe problem in most of the transition countries in our sample, and the increasing employment is one of the goals of the European Union, we expect that this issue will receive greater attention in the future. Due to the fact that regional structural developments were not sufficiently analysed, at least not in Croatia, we hope that this comparative study will contribute to the existing literature. Previous studies confirm that the economic growth during the more successful phase of transition was not strong enough to help to clear the labour market in selected countries. But these results are predominately concentrated on the country, and not on the regional level. Therefore, we analyse regional development in order to identify whether there are common patterns in Croatian regions with regions in other transition countries. We also compare our set of indicators with those in the European Union regions, particularly those geographically closer to Croatia. The main obstacle to regional analysis in Croatia is the lack of adequate statistical data. Therefore, first part of our paper consists of generating the relevant indicators. Since the paper is oriented to analysis, we do not focus on methodological problems. We are, however, aware of the limitations imposed on the interpretations of our results due to the fact. Key words: RGDP, unemployment, comparative regional analysis. JEL Classification: R19, J69, R11.
Keywords: R19; J69; R11; 330; RGDP; unemployment; comparative regional analysis